Ace your teacher interview [ 149 fantastic answers to tough interview questions - Fredericks, Anthony D. (bJist Works, 2012)
Overview: An all-in-one sourcebook of teacher interview questions in concert with the best responses to the questions most frequently asked of aspiring educators. Ace Your Teacher Interview offers specific questions and responses gathered from dozens of principals and administrators across the country, along with a creative range of inside information on what impresses interview committees.